Bioinformatics Comparison of G Protein of Isfahan Virus with the Same Proteins of Two Other Closely Related Viruses of the Genus Vesiculovirus - Mohabatkar, Hassan; Mohsenzadeh, Sasan (Protein and Peptide Letters, 2009)
Since there are not much experimental data available about different structural properties of Isfahan virus (ISFV), in the present investigation, computational study of G protein of ISFV was performed and the results were compared with G proteins of Chandipura virus (CHPV) and Piry virus (PV). Calculation of amino acid compositions of G proteins of viruses was done by PseAAC server. Predictions of localization, sequence of signal peptides, C, N and O glycosylation sites, transmembrane helices, cysteine bond positions and B cell epitopes of G proteins were performed by Virus- PLoc, Signal-CF, EnsembleGly, MemBrain, DiANNA and BCPREDS servers respectively. Similarities and differences between these glycoproteins were predicted and discussed.
Keywords: Bioinformatics